Kajian keberkesanan perlaksanaan programlatihan industri diploma pengurusan pelancongan Politeknik Johor Bahru - Zainal, Rizuan (2003)
Industrial training program is one of the important subjects for certificate and diploma courses offered in polytechnic. According to the statement, the thesis is been produced in order to make a survey on the effectiveness of the industrial training programme, which has done by Diploma in Tourism Management, Politeknik Johor Bahru students. The objectives of the survey are to know the industrial training programme fulfilled the course as well as institutions requirements; to know about the relationship and cooperation between polytechnic and industries toward providing proper training activities; to know about the suitability between the course and the training program provided by industries; and to view the solutions for the questions in order to improvise the effectiveness of industrial training. This survey was done at Politeknik Johor Bahru where all Diploma students in Tourism Management Part 5 and 6 session 2002/2003 are involved as respondents. The students must also do their industrial training programme to be qualified. Questionnaire will be used as the instrument to gain research data. While SPSS version 10.0 software has been used to do the data processing and analyzing. The prototype product has been produced according to suggestions from the past research as well as from the data gained towards improving the quality of the industrial training programme.